Zinc Oxide Nanoparticles Induce Ferroptotic Neuronal Cell Death in vitro and in vivo - Qin X (Dove Medical Press, 2020)
Xia Qin,1,* Qianghu Tang,2,* Xuejun Jiang,3,* Jun Zhang,4 Bin Wang,4 Xuemei Liu,2 Yandan Zhang,4 Zhen Zou,4,5 Chengzhi Chen2,5 1Department of Pharmacy, The First Affiliated Hospital of Chongqing Medical University, Chongqing 400016, People’s Republic of China; 2Department of Occupational and Environmental Health, School of Public Health and Management, Chongqing Medical University, Chongqing 400016, People’s Republic of China; 3Center of Experimental Teaching for Public Health, Experimental Teaching and Management Center, Chongqing Medical University, Chongqing 400016, People’s Republic of China; 4Institute of Life Sciences, Chongqing Medical University, Chongqing 400016, People’s Republic of China; 5Dongsheng Lung-Brain Disease Joint Lab, Chongqing Medical University, Chongqing 400016, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhen Zou; Chengzhi Chen Email zouzhen@cqmu.edu.cn; chengzhichen@cqmu.edu.cnPurpose: Zinc oxide nanoparticles (ZnONPs) are one of the most important nanomaterials that are widely used in the food, cosmetic and medical industries. Humans are often exposed to ZnONPs via inhalation, and they may reach the brain where neurotoxic effects could occur via systemic distribution. However, the mechanisms underlying how ZnONPs produce neurotoxic effects in the brain remain unclear. In this study, we aimed to investigate the novel mechanism involved in ZnONPs-induced neurotoxicity.Methods and Results: We demonstrated for the first time that pulmonary exposure to ZnONPs by intratracheal instillation could trigger ferroptosis, a new form of cell death, in the neuronal cells of mouse cerebral cortex. A similar phenomenon was also observed in cultured neuron-like PC-12 cell line. By using a specific inhibitor of ferroptosis ferrostatin-1 (Fer-1), our results showed that inhibition of ferroptosis by Fer-1 could significantly alleviate the ZnONPs-induced neuronal cell death both in vivo and in vitro. Mechanistic investigation revealed that ZnONPs selectively activated the JNK pathway and thus resulted in the ferroptotic phenotypes, JNK inhibitor SP600125 could reverse lipid peroxidation upregulation and ferroptotic cell death induced by ZnONPs in PC-12 cells.Conclusion: Taken together, this study not only demonstrates that pulmonary exposure of ZnONPs can induce JNK-involved ferroptotic cell death in mouse cortex and PC-12 cells, but also provides a clue that inhibition of ferroptosis by specific agents or drugs may serve as a feasible approach for reducing the untreatable neurotoxicity induced by ZnONPs.Keywords: zinc oxide nanoparticles, ferroptosis, neuron, cerebral cortex